Sépulture et rapatriement des corps des étrangers dans le royaume des Deux-Siciles (1816-1860) - Diego Carnevale (Diasporas: Circulations, Migrations, Histoire, 2017)
This article aims to understand how non-Catholic foreign communities dwelling in confessional states of nineteenth-century Europe celebrated the burial of their members. In order to analyse these dynamics, the case in point here is the Kingdom of the Two Sicilies, considered by contemporary European public opinion as a frontier space, characterized by religious conservatism. The period under consideration, namely the central decades of the century, is characterized by the diffusion of the new, simpler and more efficient, methods of embalming, which made it possible to move corpses over long distances before they decomposed. This phenomenon, albeit an initially very limited one, accounts for broader changes in attitudes towards death.